Avoiding mandatory COVID-19 vaccination: Arrogance toward science and lack of respect for common sense - Draškić Marija (Anali Pravnog Fakulteta u Beogradu)
This paper is a continuation of the research that the author started several years ago and which was published in the article Compulsory Vaccination of Children: Rights of Patients or Interests of Public Health? The emphasis will be on professional and scientific discussions on whether it is permissible to prescribe mandatory vaccination during the COVID-19 pandemic, as well as whether this is in line with the Constitution and legally allowed for all or only for certain population categories in Serbia. Earlier decisions of the constitutional courts of Serbia, Croatia, and Slovenia, as well as the recent judgment of the ECtHR in the Vavřička case will be reconsidered. All these decisions by the highest national courts, as well as the judgment of the European Court of Human Rights, have unequivocally confirmed that mandatory vaccination is not contrary to some basic human rights regularly invoked by opponents of vaccination.